Uma análise dos determinantes municipais na concessão dos auxílios estudantis no Instituto Federal de Educação, Ciência e Tecnologia do Ceará - Araújo Neto, João Cavalcante de (2024)
This dissertation aims to analyze and identify the municipal characteristics that determine the allocation of student assistance at the campuses of the Federal Institute of Education, Science, and Technology of Ceará (IFCE). The analysis period spans from 2014 to 2021, examining the quantities of student aid granted as a function of socioeconomic and demographic variables of the municipalities, using a count data regression methodology. The implementation of student assistance policies that consider the specific needs of each student is essential to strengthening social inclusion and democratizing higher education in Brazil. This study proposes a model based on municipal characteristics, offering a new perspective compared to most existing research, which focuses on the effects of aid on individuals. The models indicate that factors such as the participation of agriculture and industry in the Gross Value Added (GVA), population density, and local health and education infrastructure have a significant impact on the amount of aid distributed. These findings can serve as a basis for more efficient management of public policies and student assistance budgets.